Atorvastatin Treatment Does Not Alter Pulse Wave Velocity in Healthy Adults. (13th November 2014) - Ballard, Kevin D.; Taylor, Beth A.; Capizzi, Jeffrey A.; Grimaldi, Adam S.; White, C. Michael; Thompson, Paul D.
Abstract : Introduction . Both statins and regular physical activity (PA) reduce arterial stiffness. The present post hoc analysis examined if arterial stiffness was improved with high-dose atorvastatin treatment in healthy adults and whether PA levels magnified this response. We utilized data from a double-blind, random-assignment clinical trial investigating the effects of atorvastatin 80 mg/d for 6 mo on skeletal muscle symptoms. Methods . Central and peripheral arterial pulse wave velocity (PWV) were measured and PA levels assessed at baseline and 6 mo in subjects randomized to atorvastatin ( n = 21, 9 men) or placebo ( n = 29, 16 men). Results . Baseline participant characteristics, PWV, and PA levels were not different between treatments. Central (means ± SD; 8.7 ± 2.6 to 9.0 ± 2.5 m/sec) and peripheral PWV ( 9.9 ± 1.3 to 9.8 ± 1.6 m/sec) were unchanged from baseline following atorvastatin treatment (time × drug interaction: P ≥ 0.13 ) . Similarly, PA levels were unaffected by time or treatment. In sex and age adjusted models, baseline levels of PA were not related to changes in PWV with atorvastatin treatment. Conclusion . These data indicate that high-dose atorvastatin treatment for 6 mo does not influence arterial stiffness in healthy adults. Participation in habitual PA did not magnify the vascular effects of statin therapy. This study was registered with ClinicalTrials.gov NCT00609063 .